Employer-employee relations and employee engagement in a tertiary institution in Benin-City, Edo State - Arimie, Chukwuyem Joel (Annals of Management and Organization Research, 2019)
Purpose: This study aimed to explore the relationship between employer-employee relations and employee engagement in a tertiary institution in Edo State. Research methodology: Semi-structured interviews were conducted on a cross-section of management staff, heads of department, and units in the University. A descriptive method was adopted for data analysis. Results: The results of this study revealed that employee engagement is a by-product of employer-employee relations and the quality of the relationship is one of the most critical factors that drive engagement and satisfaction of employees. Limitations: The challenge was the inadequate number of respondents interviewed due to time constraint. Contribution: The study provided insight into the so called "soft aspect" of an organization and the way people relate with one another, and advocated the need for employers, managers, and supervisors in organizations to recognize the emotional composite of an employee, and the creation of a healthy relationship that would meet the employee' emotional needs. Keywords: Effective employer-employee relations, Engagement, Psychological needs, Productivity